Fertilization of Field-Grown and Landscape Palms in Florida - Timothy K. Broschat (EDIS)
Palms growing in Florida landscape or field nurseries are subject to a number of potentially serious nutrient deficiencies. This revised 5-page document discusses the prevention and treatment of these deficiencies. Written by Timothy K. Broschat and published by the Environmental Horticulture Department, November 2016.